Images of Rosie: A Content Analysis of Women Workers in American Magazine Advertising, 1940–1946 - Lewis, Charles; Neville, John (Journalism & Mass Communication Quarterly, 1995)
This study, based on a content analysis of magazine advertising images of women during the World War II era, has two purposes. One is to help determine whether advertisers made a concerted change in their shaping of women's images during and after World War II. The other purpose is to indicate further research on the topic of women and advertising during the war years. This examination is an initial attempt to better explain the relationship between the advertising industry, the actual “reality” of working women, and sociocultural constructions of female gender identity immediately before, during, and immediately following World War II.
Keywords: Business History and gender